Extending OCL Operation Contracts with Objective Functions - Krieger, Matthias; Brucker, Achim (Electronic Communications of the EASST, 2011)
We explore the potential of adding objective functions to OCL operation contracts. If an operation contract includes an objective function, the operation has the obligation to yield results that make the objective function assume an optimal value. Thus, an objective function expresses a preference among the possible operation results that conform to the postconditions of the operation contract and any class invariants. Objective functions strictly increase the expressiveness of OCL operation contracts. While objective functions arise naturally in application domains like operations research, we argue that objective functions are a useful general-purpose specification instrument and discuss several application examples. As tool support for operation contracts with objective functions, we present an animator for OCL operation contracts with optimization capabilities. We ensure tool interoperability by specifying objective functions in a UML profile.